Development of Augmented Reality-Based Learning Media on Mechanical Wave Material - Hafirizka Hafirizka; Muhammad Nasir; Muhammad Syafi’i (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
Augmented reality is one of the most potential technologies for education. Especially in learning Physics for material that is not real. Wave material is one of the appropriate topics if we study it using augmented reality media. The purpose of this research is to develop, validate, and check the reliability of augmented reality-based learning media on mechanical wave material. This research is an R&D research using the ADDIE-type instructional design model. This augmented reality-based media was designed using the Blender, Vuforia, and Unity applications. The Blender application is used to create 3D wave models, Vuforia to create markers, and Unity to create the final application that is displayed on students' androids. This research has produced a 46-page wave material physics module that is integrated with an augmented reality application consisting of 17 markers about waves. The size of the application is 222 Mb with the Apk format on Android version 4.1 Jelly Bean and a 13 MP camera. After testing the validity with 3 experts (experts), namely media experts, material experts, and pedagogic experts as well as 3 expert users (expert users), the average value of an expert and user experts is 4.5 and 4.8 with a maximum score of 5. Media This was also assessed as good by 20 student responses. So that this learning media can be said to be valid according to experts, expert users, and users.